2017
DOI: 10.1016/j.prostaglandins.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Integrating multi-omics biomarkers and postprandial metabolism to develop personalized treatment for anorexia nervosa

Abstract: Background Anorexia nervosa (AN) is a serious mental illness characterized by emaciation, an intense fear of gaining weight despite being underweight, and distorted body image. Few treatments reverse the core symptoms in AN such as profound aversion to food and food avoidance. Consequently, AN has a chronic and relapsing course and the highest mortality rate of any psychiatric illness. A more complete understanding of the disease pathogenesis is needed in order to develop better treatments and improve AN outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…Muller et al also identified similar clinical benefits of celecoxib as adjunctive treatment during the middle of the treatment course, and demonstrated the activation of the type-1 immune response coupling to down-regulation of the type-2 immune response mediated by celecoxib as a potential mechanism of action [98]. Our eicosanoid data which showed AN had a hyper postprandial responsiveness to ARA compared to healthy controls suggests that food-associated inflammatory processes may increase anxiety and pain, contributing to psychopathological eating behavior in AN [16]. In light of the aberrant PUFAs identified in AN (Table 1), a better understanding of how PUFAs interact with host factors (e.g., genetic variation) to modulate eicosanoid-induced inflammation in AN can provide much-needed knowledge to develop optimum PUFA formulation to improve AN symptoms and treatment outcomes.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Muller et al also identified similar clinical benefits of celecoxib as adjunctive treatment during the middle of the treatment course, and demonstrated the activation of the type-1 immune response coupling to down-regulation of the type-2 immune response mediated by celecoxib as a potential mechanism of action [98]. Our eicosanoid data which showed AN had a hyper postprandial responsiveness to ARA compared to healthy controls suggests that food-associated inflammatory processes may increase anxiety and pain, contributing to psychopathological eating behavior in AN [16]. In light of the aberrant PUFAs identified in AN (Table 1), a better understanding of how PUFAs interact with host factors (e.g., genetic variation) to modulate eicosanoid-induced inflammation in AN can provide much-needed knowledge to develop optimum PUFA formulation to improve AN symptoms and treatment outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…Our multi-omics studies in AN [15,16] demonstrated for the first time that similar to cancer [77,78], PUFA and PUFA-associated eicosanoids play a role not only in AN risk but may also effect comorbid psychopathology [15] and postprandial metabolism dysregulation [79]. The increased activity of soluble epoxide hydrolase (sEH) observed in both ill and recovered AN patients compared to controls [15,16] implicates cellular inflammation as a key risk factor or disease modulator for AN.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations